1965
DOI: 10.1017/s0022112065000320
|View full text |Cite
|
Sign up to set email alerts
|

The dispersion and attenuation of helicon waves in a uniform cylindrical plasma

Abstract: A systematic account is given of the derivation of the dispersion relation for helicon waves in a uniform cylindrical plasma bounded by a vacuum. By retaining finite resistivity in the equations, boundary conditions present no difficulties, since the wave magnetic field is continuous through the plasma-vacuum interface. Two unexpected results are found. First, the wave attenuation remains finite in the limit of vanishing resistivity. This is due to the energy dissipated at the interface by the surface currents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
1

Year Published

1967
1967
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(64 citation statements)
references
References 8 publications
1
62
0
1
Order By: Relevance
“…This dispersion relation was first derived by Klozenberg et al 11 Both waves satisfy the Helmholtz equation,…”
Section: ͑4͒mentioning
confidence: 90%
See 1 more Smart Citation
“…This dispersion relation was first derived by Klozenberg et al 11 Both waves satisfy the Helmholtz equation,…”
Section: ͑4͒mentioning
confidence: 90%
“…Klozenberg et al 11 found an unexpected wave attenuation in a helicon wave study, for which the electrical resistivity term in the equations was not involved. They reported the surface current required at the boundary of the plasma needed to match the plasma wave field to the vacuum wave field.…”
Section: Introductionmentioning
confidence: 99%
“…For example helicon waves have a wavenumbers in azimuthal direction, radial direction and parallel direction along the ambient field B 0 . They have been studied in solid state plasmas [3] and in gaseous plasma columns [4] which opened up many applications [5,6]. In spite of a vast body of literature on helicons no measurements of magnetic field lines have been reported, partly because in-situ field line measurements are impossible in solid state plasmas or space plasmas.…”
mentioning
confidence: 99%
“…Some 50 years ago waves with similar properties were observed in magnetized solids [8]. Whistler modes were also excited in discharge plasmas produced in the laboratory [9]. The waves in bounded plasma columns were termed 'helicons' [10] and a new specialty of low temperature plasma applications evolved [11].…”
Section: Brief Historical Backgroundmentioning
confidence: 99%